The state of apprenticeship in 2010 : international comparisons: Australia, Austria, England, France, Germany, Ireland, Sweden, Switzerland - Steedman, Hilary [Verfasser] (My University, 2010)
This report provides an overview of apprenticeship in eight European countries and Australia. Each chapter in this publication is structured in the same way. Chapters may be read as stand-alone studies without reference to the full Report. All chapters use the same headings in the same order as follows: school system; post-compulsory vocational routes; governance and content; apprentice occupation; completion and progression; careers guidance; quality of entrants; demand for apprenticeship; funding apprenticeship. (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; I 2.2.1 Westeuropa; I 2.3.5 Australien, Ozeanien; Berufsausbildung; Ausbildungsstellenmarkt; Internationaler Vergleich; Quantitative Angaben; England; Australien; Österreich; Frankreich; Bundesrepublik Deutschland; Irland; Schweden; Schweiz